Anethum graveolens (dill) – A medicinal herb induces apoptosis and cell cycle arrest in HepG2 cell line. (12th June 2018) - Mohammed, Furkhan Ahmed; Elkady, Ayman I.; Syed, Fareeduddin Quadri; Mirza, Muqtadir Baig; Hakeem, Khalid Rehman; Alkarim, Saleh
Abstract: Ethnopharmacological relevance: The medicinal herb, Anethum graveolens L. (dill) is one of the potent culinary herbs used as an alternative form of medicine worldwide. The unguent topical Oil from the aerial parts of A. graveolens was found to be effective in the management of uterus cancer in ethnomedicine has been reported. Background: The incidence and mortality rates of Hepatocellular carcinoma (HCC) are steadily rising worldwide, especially, in underdeveloped and developing countries. Moreover, HCC develops rapidly in patients with chronic cirrhosis or hepatitis, where the solid tumours/malignancies coexist with the inflammation. Recent studies have shown that the medicinal herb, Anethum graveolens, holds anticancer potential, which could be a promising approach for the treatment of various tumours. Aim: In the current study, we have analysed the antiproliferative effect of ethyl acetate fraction of Dill Seeds (EAFD) on HepG2 cell line. Methods: Cell viability and proliferation were observed by MTT assay; Morphological changes were studied using fluorescent stains like Hoechst 33342, acridine orange/ethidium bromide and JC-1 dye. Further, the pro-apoptotic activity was demonstrated through Annexin-V-FITC/ PI assay and cell cycle analysis. Different concentrations (0.1, 0.2, 0.4, 0.6, 0.8 mg/ ml) of EAFD were studied. Results: EAFD markedly suppressed the proliferation of HepG2 cells in a dose and time-dependent manner. The phase contrast and fluorescence microscopy revealed the morphological alterations like disruption, shrinkage, detachment and blebbing of cell membrane accompanied by nuclear condensation after exposure to EAFD. Radical scavenging activity was evidenced by measurement of ROS levels post-treatment. Modulation of mitochondrial membrane potential was exhibited leading to the activation of caspases 3/7 and 9 which is a committed step towards apoptosis. Annexin V-FITC/ PI assay and cell cycle, later confirmed the apoptosis and cell cycle arrest in 'G2/M' phase through flow cytometric analysis. Conclusion: In conclusion, a significant apoptogenic effect was exhibited by EAFD against HepG2 cells in inducing apoptosis and cell cycle arrest. Our findings indicate that the medicinal herb- Anethum graveolens, holds potential in treating hepatocellular carcinoma effectively. Graphical abstract: fx1